Sodium Butyrate Ameliorates Gut Microbiota Dysbiosis in Lupus-Like Mice - Hanchang He; Haoming Xu; Jing Xu; Hailan Zhao; Qianyun Lin; Youlian Zhou; Yuqiang Nie (2020)
Gut microbiota has a strong influence on the onset and development of systemic lupus erythematosus (SLE), and several studies have demonstrated the effectiveness of microbiota-derived butyrate to ameliorate SLE. However, the roles of butyrate on gut microbiota in SLE are not understood. Using MRL/lpr lupus-prone mice, we examined gut microbiota profiles after butyrate treatment by 16S rRNA sequencing. Alterations in intestinal microbiome in mice with lupus-like disease were mainly characterized by a reduction in microbial diversity, with an increased abundance of Bacteroidetes and a decrease of Firmicutes. Treatment of lupus-prone mice with butyrate resulted in increased abundance of Firmicutes (P=0.003), Clostridia (P=0.005), Clostridiales (P=0.005), Lachnospiraceae (P=0.009), Ruminococcaceae (P=0.021), Peptostreptococcaceae (P=0.021), Ruminiclostridium (P=0.016), Oscillibacter (P=0.048), Romboutsia (P=0.025), Lachnoclostridium (P=0.012), Coprococcus (P=0.015), Ruminococcus (P=0.011), Clostridium leptum (P< 0.05), and Dorea_spp. (P=0.019), and a reduced proportion of Bacteroidetes (P=0.004), Bacteroidia (P=0.004), and Bacteroidales (P=0.004). Further, butyrate supplementation could ameliorate kidney damage. Overall, this study suggests that gut microbiota alterations occur in MRL/lpr lupus-prone mice following treatment with butyrate. Butyrate supplementation ameliorated gut microbiota dysbiosis. These findings support the use of butyrate and butyrate-producing bacteria as potential treatments for SLE.